A self-repairing coating material based on MOFs, a preparation method and application in a paint film protection film

CN122563468BActive Publication Date: 2026-10-27HAIAN HO CHI TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611037111.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-07-13
Publication Date
2026-10-27
Estimated Expiration
2046-07-13

AI Technical Summary

Technical Problem

[0005]为解决现有技术中MOFs基自修复涂层存在的以下技术缺陷:修复剂负载方式单一,不同修复剂在孔道内无序分布引发预反应失活;MOFs与聚合物基体间界面结合力不足,颗粒团聚与脱粘;缺乏对异氰酸酯类修复剂在涂层制备过程中的保护机制,修复活性提前消耗;修复剂释放触发机制缺乏对损伤应力的选择性响应

Benefits of technology

(1)(1)本发明通过向锆基MOFs中掺入铈离子,利用铈离子与γ-氨丙基三乙氧基硅烷中氨基之间形成的配位键,将γ-氨丙基三乙氧基硅烷选择性固定于MOFs外表面及孔道入口处的铈活性位点上,同时将(2,4,6-三氧代三嗪-1,3,5(2H,4H,6H)-三基)三(六亚甲基)异氰酸酯通过配位相互作用锚定于MOFs孔道内壁的锆氧簇节点上,由此在单一MOFs颗粒上实现了两种修复剂的空间分区负载和差异化固定。该空间分区负载模式使得(2,4,6-三氧代三嗪-1,3,5(2H,4H,6H)-三基)三(六亚甲基)异氰酸酯在涂层制备过程中受到孔道内壁的物理屏蔽和γ-氨丙基三乙氧基硅烷在孔道入口处形成的分子阻挡层双重保护,有效避免了异氰酸酯基团在涂层紫外光固化阶段与体系中含活泼氢组分发生非预期副反应,从而在涂层制备完成状态下保持了(2,4,6-三氧代三嗪-1,3,5(2H,4H,6H)-三基)三(六亚甲基)异氰酸酯修复活性的完整保留。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122563468B_ABST
    Figure CN122563468B_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of functional coating materials, and particularly relates to a self-repairing coating material based on MOFs, a preparation method and application in a paint surface protection film. The preparation method comprises the following steps: preparing a UiO-66 type cerium doped zirconium based MOFs carrier material by reacting zirconium salt, cerium salt and terephthalic acid; the carrier material is sequentially reacted with (2,4,6-trioxotriazine-1,3,5(2H,4H,6H)-triyl)tris(hexamethylene) isocyanate and gamma-aminopropyl triethoxysilane to obtain a MOFs composite material loaded with double repair agents; and the MOFs composite material loaded with double repair agents is added into a mixed solvent together with polyurethane acrylate, dipentaerythritol hexaacrylate, trimethylolpropane triacrylate, a photoinitiator and a leveling agent to obtain the self-repairing coating material based on MOFs. The coating material prepared by the application has self-repairing performance and good mechanical integrity, and is suitable for fields such as paint surface protection films.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of functional coating materials technology, specifically relating to a self-healing coating material based on MOFs, its preparation method, and its application in paint protective films. Background Technology

[0002] Paint protection films, as key materials for surface protection in automobiles, aerospace, and high-end electronic devices, primarily function to resist scratches, gravel impacts, and chemical corrosion generated during daily use, thereby maintaining the substrate's appearance integrity and value over a long period. Traditional paint protection films mainly consist of a polyurethane substrate and a surface coating, relying on their physical toughness and hardness to provide passive protection. However, after suffering minor damage, surface scratches are difficult to repair spontaneously, and the protective performance continuously declines with accumulated damage, severely limiting service life and aesthetic maintenance. Therefore, developing intelligent protective materials with active repair capabilities has become an important development direction in the field of functional films.

[0003] Imparting self-healing ability to coatings is an effective way to solve the above problems. At present, the mainstream technical route is to introduce repair agent carriers such as microcapsules or hollow fibers into the coating. When the coating is damaged, the carrier breaks and releases the repair agent to achieve healing. However, this method has problems such as limited repair times, poor compatibility between the carrier and the substrate, and premature leakage. In recent years, metal-organic frameworks (MOFs) have attracted widespread attention as novel nanocontainers due to their high specific surface area, tunable pore structure and abundant metal active sites. Studies have shown that MOFs can efficiently load corrosion inhibitors or repair monomers through adsorption or coordination and achieve responsive release under specific environmental stimuli (such as pH changes and humidity), showing active protection potential. However, existing MOF-based self-healing coatings generally face the following technical defects: (1) The repair agent loading method is single and lacks spatial partition loading design. Existing technologies usually rely only on the physical adsorption of MOF pores to load a single repair agent. Different repair agent molecules are randomly distributed in MOF pores and are prone to pre-reaction with each other, resulting in partial deactivation of the repair agent during the coating preparation stage. Meanwhile, a single adsorption method cannot achieve differentiated fixation of different types of repair agents, resulting in a lack of selectivity in the release behavior of the repair agents. Unexpected leakage is likely to occur during the service of the coating, which seriously affects the long-term stability of the coating. (2) Insufficient interfacial bonding between MOFs and the polymer matrix. In the existing technology, MOF particles are only physically blended and dispersed in the polymer matrix. There is a lack of chemical bond between the non-coordinating metal active sites on the surface of MOFs and the polymer molecular chains, which leads to the aggregation and sedimentation of MOF particles during the coating curing process, resulting in poor dispersion uniformity. At the same time, physically blended MOF particles are easily detached from the polymer matrix when the coating is subjected to external force, forming new interfacial defects, which weakens the mechanical integrity of the coating. (3) Lack of protection mechanism for isocyanate repair agents in the coating preparation process. Isocyanate groups have high reactivity and are prone to side reactions with components containing active hydrogen (such as water, alcohol, carboxylic acid, etc.) in the system during the preparation and curing of the coating slurry, resulting in premature consumption of repair activity. Existing technologies lack effective shielding and protection methods, causing a large amount of isocyanate-based repair agents loaded in MOFs to become inactive before the coating is completed, greatly reducing the self-healing effect. (4) The triggering mechanism for the release of repair agents is singular and lacks selective response to damage stress. Existing technologies mainly rely on changes in ambient humidity or pH to trigger the release of repair agents. These release conditions are not directly related to the local physicochemical changes when the coating is actually damaged, resulting in the repair agent continuously and slowly leaking under non-damaged conditions, while insufficient release occurs in the scratched areas that actually need repair.

[0004] In summary, existing self-healing coating technologies still have limitations in terms of carrier structure design, interface compatibility, repair agent protection, and response selectivity, making it difficult to meet the comprehensive requirements of paint protection films for self-healing performance and adaptability to complex service environments. Summary of the Invention

[0005] To address the following technical shortcomings of existing MOF-based self-healing coatings: a single loading method for the repair agent, leading to disordered distribution of different repair agents within the pores and resulting in pre-reaction deactivation; insufficient interfacial bonding between MOFs and the polymer matrix, causing particle agglomeration and debonding; lack of a protective mechanism for isocyanate-based repair agents during coating preparation, leading to premature depletion of repair activity; and a lack of selective response to damage stress in the repair agent release triggering mechanism, this invention provides a MOF-based self-healing coating material, its preparation method, and its application in paint protective films.

[0006] To achieve the above objectives, the technical solution adopted by the present invention is as follows: A method for preparing a self-healing coating material based on MOFs includes the following steps: Step 1: React zirconium salt and cerium salt with terephthalic acid to prepare UiO-66 type cerium-doped zirconium-based MOF support material; Step 2: Disperse the UiO-66 type cerium-doped zirconium-based MOFs support material in n-hexane, add (2,4,6-trioxotriazine-1,3,5(2H,4H,6H)-triyl)tris(hexamethylene)isocyanate, stir, and after stirring is completed, add γ-aminopropyltriethoxysilane and continue the reaction. After the reaction is completed, separate, wash and dry to obtain the MOFs composite material loaded with dual repair agents. Step 3: The MOFs composite material loaded with dual repair agents is added to a mixed solvent along with polyurethane acrylate, dipentaerythritol hexaacrylate, trimethylolpropane triacrylate, photoinitiator and leveling agent. After dispersion treatment, a self-healing coating material based on MOFs is obtained.

[0007] Preferably, step one specifically includes: Zirconium and cerium salts were dissolved in N,N-dimethylformamide to obtain a mixed metal salt solution; terephthalic acid was dissolved in N,N-dimethylformamide to obtain an organic ligand solution; the organic ligand solution was added dropwise to the mixed metal salt solution, stirred, and then transferred to a reaction vessel. After the reaction was completed, the mixture was cooled, centrifuged, washed, and dried to obtain UiO-66 type cerium-doped zirconium-based MOFs support material.

[0008] Preferably, the molar ratio of zirconium salt to cerium salt is 1:(0.1-0.5), the molar amount of terephthalic acid in the organic ligand solution is twice the sum of the molar amounts of zirconium salt and cerium salt in the mixed metal salt solution, and the reaction conditions are 6-18 h at a temperature of 80-120℃.

[0009] Preferably, the zirconium salt includes zirconium tetrachloride, the cerium salt includes cerium nitrate, and when preparing the mixed metal salt solution, the amount of N,N-dimethylformamide used is such that the concentration of zirconium salt in the mixed metal salt solution is 0.05-0.15 mol / L.

[0010] Preferably, when preparing the organic ligand solution, the amount of N,N-dimethylformamide used is such that the concentration of terephthalic acid in the organic ligand solution is 0.05-0.2 mol / L.

[0011] Preferably, in step two, the mass ratio of (2,4,6-trioxotriazine-1,3,5(2H,4H,6H)-triyl)tris(hexamethylene)isocyanate, γ-aminopropyltriethoxysilane, and UiO-66 type cerium-doped zirconium-based MOFs support material is (1-3):(0.2-0.8):1. The stirring conditions are: stirring at 30-50℃ at a speed of 400-600 r / min for 3-8 h; and continued stirring at 30-50℃ at a speed of 400-600 r / min for 1-4 h.

[0012] Preferably, in step two, the mass-to-volume ratio of the UiO-66 type cerium-doped zirconium-based MOFs support material to n-hexane is 1 g / (40-80) mL.

[0013] Preferably, in step two, (2,4,6-trioxotriazine-1,3,5(2H,4H,6H)-triyl)tri(hexamethylene)isocyanate is added in the form of a hexane dilution, wherein the volume ratio of (2,4,6-trioxotriazine-1,3,5(2H,4H,6H)-triyl)tri(hexamethylene)isocyanate to hexane in the hexane dilution is 1:(2-5).

[0014] UiO-66 is a metal-organic framework (MOF) material with Zr 4+ With ions as the metal center and terephthalic acid (H₂BDC) as the organic ligand, a stable three-dimensional framework structure is formed. Its basic structural unit is the octahedral Zr₆O₄(OH)₄ cluster. In cerium-doped zirconium-based MOF support materials, Ce… 3+ It is located on the six-core metal-oxygen cluster node of UiO-66 type MOFs in a replacement manner, occupying the space originally belonging to Zr 4+ The lattice positions of Ce were determined, and (Ce) was formed. x Zr6-x The structure is a mixed metal cluster of O4(OH)4. The mechanism of cerium doping is: Ce 3+ With Zr 4+ Similar in size, it can partially replace Zr in the cluster. 4+ This leads to a charge imbalance and induces the formation of oxygen vacancies (Zr-O-Ce bonds are weakened, and oxygen leaves the lattice).

[0015] Based on the bimetallic node characteristics of this structure, the differentiated anchoring of the two remedial agent molecules in step two is achieved through the following mechanism: the first added (2,4,6-trioxotriazine-1,3,5(2H,4H,6H)-triyl)tri(hexamethylene)isocyanate molecule is relatively large. Under conditions of no competitive adsorption, the isocyanate group (-N=C=O) in its molecule contains nitrogen and oxygen atoms with lone pairs of electrons, which can act as Lewis bases and preferentially bind to the coordinatingly unsaturated Zr on the zirconium-oxygen cluster nodes on the inner wall of the pore due to ligand deficiency or structural defects. 4+ The ions (with empty d orbitals) form coordination interactions with each other, thereby being anchored to the zircon sites on the inner wall of the pores; (2) the primary amino group (-NH2) in the added γ-aminopropyltriethoxysilane molecule contains a nitrogen atom with a lone pair of electrons, which can act as a Lewis base and mainly interact with Ce exposed on the outer surface of MOFs and at the pore entrance. 3+ Coordinate bonds are formed between ions (with empty f orbitals), thereby fixing the γ-aminopropyltriethoxysilane molecule to the cerium site. 3+ The ion has an empty f orbital, which can act as a Lewis acid to accept the lone pair of electrons donated by the nitrogen atom in the primary amino group, forming a coordinate bond. Meanwhile, Ce... 3+ Replace Zr 4+ The oxygen vacancies generated thereafter further enhance its activity as a Lewis acid site, which is beneficial for the coordination anchoring of amino groups.

[0016] Preferably, in step three, the mass ratio of the MOFs composite material loaded with dual repair agents to polyurethane acrylate is 1:(15-35); the amount of dipentaerythritol hexaacrylate is 3%-10% of the mass of polyurethane acrylate; the amount of trimethylolpropane triacrylate is 1%-5% of the mass of polyurethane acrylate; the amount of photoinitiator is 0.5%-2% of the mass of polyurethane acrylate; and the amount of leveling agent is 0.1%-0.5% of the mass of polyurethane acrylate.

[0017] Preferably, in step three, the photoinitiator is 2-hydroxy-2-methyl-1-phenylpropanone, the leveling agent is polyether-modified polydimethylsiloxane, and the mixed solvent is prepared by mixing butyl acetate and propylene glycol methyl ether acetate in a volume ratio of (3-1):1; the amount of the mixed solvent is such that the solid content of the MOF-based self-healing coating material is 40%-55%.

[0018] The present invention also discloses a self-healing coating material based on MOFs, which is prepared by the preparation method of the self-healing coating material based on MOFs as described above.

[0019] Application of a MOF-based self-healing coating material as described above on paint protection film.

[0020] Compared with the prior art, the beneficial effects of the present invention are as follows: (1) In this invention, cerium ions are incorporated into zirconium-based MOFs. The coordination bonds formed between cerium ions and the amino groups in γ-aminopropyltriethoxysilane are used to selectively fix γ-aminopropyltriethoxysilane onto the cerium active sites on the outer surface of MOFs and at the pore entrance. At the same time, (2,4,6-trioxotriazine-1,3,5(2H,4H,6H)-triyl)tri(hexamethylene)isocyanate is anchored to the zirconium-oxygen cluster nodes on the inner wall of the MOF pores through coordination interactions. Thus, spatial partitioning and differentiated fixation of two remediation agents are achieved on a single MOF particle. This spatial partitioning loading mode ensures that (2,4,6-trioxotriazine-1,3,5(2H,4H,6H)-triyl)tri(hexamethylene)isocyanate is protected by both the physical shielding of the pore inner wall and the molecular barrier layer formed by γ-aminopropyltriethoxysilane at the pore entrance during coating preparation. This effectively prevents unintended side reactions between the isocyanate groups and the active hydrogen-containing components in the system during the UV curing stage of the coating, thus maintaining the complete preservation of the repair activity of (2,4,6-trioxotriazine-1,3,5(2H,4H,6H)-triyl)tri(hexamethylene)isocyanate in the completed coating state.

[0021] (2) In this invention, the zirconium and cerium ion active sites located on the hexanuclear metal-oxygen cluster nodes in cerium-doped zirconium-based MOFs serve as differentiated anchoring sites for (2,4,6-trioxotriazine-1,3,5(2H,4H,6H)-triyl)tris(hexamethylene)isocyanate and γ-aminopropyltriethoxysilane, respectively. 3+ The occupied cerium sites preferentially form coordination bonds with the primary amino groups of the subsequently added γ-aminopropyltriethoxysilane, while the unsaturated Zr groups at the zirconium-oxygen cluster nodes on the inner wall of the pores are coordinated. 4+The site preferentially forms coordination interactions with the isocyanate groups of the first-added (2,4,6-trioxotriazine-1,3,5(2H,4H,6H)-triyl)tri(hexamethylene)isocyanate, thereby achieving spatially selective loading of the two repair agents on a single MOF particle. Simultaneously, cerium and zirconium ions chemically link the MOF composite particles to the polymer matrix through coordination bonds with the carbonyl oxygen groups of the urethane groups in the polyurethane acrylate crosslinking network, resulting in a uniform and stable chemically bonded dispersion of the MOF composite particles in the coating. When scratch damage occurs, (2,4,6-trioxotriazine-1,3,5(2H,4H,6H)-triyl)tri(hexamethylene)isocyanate is released from the MOF channels to the scratched area. The released isocyanate groups undergo addition reactions with the hydroxyl groups and active hydrogens of the urethane in the exposed polymer matrix at the scratch site, generating urea bonds and new urethane bonds.

[0022] (3) In this invention, (2,4,6-trioxotriazine-1,3,5(2H,4H,6H)-triyl)tris(hexamethylene)isocyanate molecules are fixed to zirconium sites on the inner wall of MOF pores via coordination interactions. When the coating is intact, these coordination interactions provide sufficient binding force to suppress spontaneous migration and leakage of the repair agent. When scratch damage occurs, local stress can disrupt these coordination interactions, thereby triggering the release of the repair agent. Compared with the release mechanism in the prior art that depends on changes in ambient humidity or pH, the release behavior of the repair agent in this invention is directly related to the damage stress, avoiding unintended leakage of the repair agent under non-damage conditions. Attached Figure Description

[0023] Figure 1 This is a SEM image of the MOFs support material prepared in Example 1 of the present invention; Figure 2 The images show the XRD patterns of the MOFs support materials prepared in Example 1 and Comparative Examples 1-2 of this invention. (a) shows the MOFs support material prepared in Comparative Example 2, (b) shows the MOFs support material prepared in Comparative Example 1, and (c) shows the MOFs support material prepared in Example 1. Detailed Implementation

[0024] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.

[0025] Example 1 This embodiment discloses a method for preparing a self-healing coating material based on MOFs, including the following steps: Step 1: Anhydrous zirconium tetrachloride (CAS No.: 10026-11-6, purity 99.9%) and cerium nitrate hexahydrate (CAS No.: 10294-41-4, purity 99.9%) were mixed at a molar ratio of 1:0.3 and then added to N,N-dimethylformamide to make the concentration of zirconium tetrachloride in the mixed metal salt solution 0.1 mol / L. The mixture was stirred at 400 r / min for 60 min at 35 °C to obtain the mixed metal salt solution. Then, terephthalic acid (CAS No.: 100-21-0, purity 99%), which is twice the sum of the molar amounts of anhydrous zirconium tetrachloride and cerium nitrate hexahydrate, was added to N,N-dimethylformamide to make the concentration of terephthalic acid in the organic ligand solution 0.12 mol / L. The mixture was stirred at 400 r / min for 30 min at room temperature to obtain the organic ligand solution. The organic ligand solution was added dropwise to the mixed metal salt solution. After the addition was complete, the mixture was stirred at 400 r / min for 120 min at room temperature. The mixture was then transferred to a stainless steel hydrothermal reactor lined with polytetrafluoroethylene. After sealing, the mixture was reacted at 100℃ for 12 h. After naturally cooling to room temperature, the solid product was obtained by centrifugation. The solid product was washed three times with N,N-dimethylformamide, with each wash volume being 10 times the volume of the solid product. The solid product was then washed three times with methanol, with each wash volume being 10 times the volume of the solid product. The solid product was dried at 100℃ in air for 24 h to obtain the UiO-66 type cerium-doped zirconium-based MOF support material. Step 2: The UiO-66 type cerium-doped zirconium-based MOF support material obtained in Step 1 was added to n-hexane at a mass-to-volume ratio of 1 g / 60 mL. The mixture was stirred at 400 r / min for 30 min at 35 °C to form a homogeneous suspension. (2,4,6-trioxotriazine-1,3,5(2H,4H,6H)-triyl)tris(hexamethylene)isocyanate (CAS No.: 3779-63-3) was added to the suspension as a hexane dilution. The hexane dilution contained (2,4,6-trioxotriazine-1,3,5(2H,4H,6H)-triyl)tris(hexamethylene)isocyanate. The volume ratio of 5(2H,4H,6H)-trimethyl)tri(hexamethylene)isocyanate to n-hexane was 1:3.5. The mixture was stirred at 500 r / min for 5.5 h at 40 °C. After stirring, γ-aminopropyltriethoxysilane (CAS No.: 919-30-2, purity 98%) was added, and stirring was continued at 500 r / min for 2.5 h at 40 °C. After stirring, the solid product was obtained by centrifugation and washed three times with n-hexane, each time with an amount of 8 times the volume of the solid product. The product was dried at 50 °C under a nitrogen atmosphere for 10 h to obtain the MOF composite material loaded with dual repair agents. The mass ratio of (2,4,6-trioxotriazine-1,3,5(2H,4H,6H)-triyl)tris(hexamethylene)isocyanate, γ-aminopropyltriethoxysilane, and UiO-66 type cerium-doped zirconium-based MOFs support material is 2:0.5:1. Step 3: Combine the MOFs composite material loaded with dual repair agents obtained in Step 2 with aliphatic polyurethane acrylate (Zhanxin, EBECRYL®). 230, functionality 2, viscosity at 60℃ is 350-650 mPa·s.), dipentaerythritol hexaacrylate (CAS No.: 29570-58-9, purity 98%), trimethylolpropane triacrylate (CAS No.: 15625-89-5, purity 98%), photoinitiator 2-hydroxy-2-methyl-1-phenylpropanone (CAS No.: 7473-98-5, purity 99%), and leveling agent polyether modified polydimethylsiloxane (BYK-3455, non-volatile content (10min, 150℃) > 90%) were added to a mixed solvent (prepared by mixing butyl acetate and propylene glycol methyl ether acetate at a volume ratio of 3:1). The mixture was stirred and dispersed at 2000 r / min for 30 min at 35℃ to obtain a self-healing coating material based on MOFs. In this process, the mass ratio of the MOFs composite material loaded with dual repair agents to polyurethane acrylate is 1:25; the amount of dipentaerythritol hexaacrylate is 6.5% of the mass of polyurethane acrylate; the amount of trimethylolpropane triacrylate is 3% of the mass of polyurethane acrylate; the amount of photoinitiator 2-hydroxy-2-methyl-1-phenylpropanone is 1.5% of the mass of polyurethane acrylate; the amount of leveling agent polyether-modified polydimethylsiloxane is 0.3% of the mass of polyurethane acrylate; and the amount of mixed solvent is such that the solid content of the MOFs-based self-healing coating material is 48%.

[0026] Example 2 This embodiment discloses a method for preparing a self-healing coating material based on MOFs, including the following steps: Step 1: Anhydrous zirconium tetrachloride and cerium nitrate hexahydrate are mixed at a molar ratio of 1:0.1 and then added to N,N-dimethylformamide to make the concentration of zirconium tetrachloride in the mixed metal salt solution 0.05 mol / L. The mixture is stirred at 400 r / min for 60 min at 35 °C to obtain the mixed metal salt solution. Then, terephthalic acid, at a molar ratio twice that of the sum of anhydrous zirconium tetrachloride and cerium nitrate hexahydrate, is added to N,N-dimethylformamide to make the concentration of terephthalic acid in the organic ligand solution 0.05 mol / L. The mixture is stirred at 400 r / min for 30 min at room temperature to obtain the organic ligand solution. The organic ligand solution was added dropwise to the mixed metal salt solution. After the addition was complete, the mixture was stirred at 400 r / min for 120 min at room temperature. The mixture was then transferred to a polytetrafluoroethylene-lined stainless steel hydrothermal reactor, sealed, and reacted at 80℃ for 18 h. After natural cooling to room temperature, the solid product was obtained by centrifugation. The solid product was washed three times with N,N-dimethylformamide, with each wash volume being 10 times the volume of the solid product. The solid product was then washed three times with methanol, with each wash volume being 10 times the volume of the solid product. The solid product was dried at 100℃ in air for 24 h to obtain the UiO-66 type cerium-doped zirconium-based MOF support material. Step two: The UiO-66 type cerium-doped zirconium-based MOF support material obtained in step one is added to n-hexane at a mass-to-volume ratio of 1 g / 40 mL. The mixture is stirred at 35°C and 400 r / min for 30 min to form a homogeneous suspension. (2,4,6-trioxotriazine-1,3,5(2H,4H,6H)-triyl)tris(hexamethylene) isocyanate is added to the suspension as a hexane dilution. The (2,4,6-trioxotriazine-1,3,5(2H,4H,6H)-triyl)tris(hexamethylene) isocyanate in the hexane dilution... A 1,3,5(2H,4H,6H)-triyl)tri(hexamethylene)isocyanate was mixed with n-hexane at a volume ratio of 1:2. The mixture was stirred at 600 r / min for 3 h at 50 °C. After stirring, γ-aminopropyltriethoxysilane was added, and stirring was continued at 600 r / min for 1 h at 50 °C. After stirring, the solid product was obtained by centrifugation and washed three times with n-hexane, each time with an amount of 8 times the volume of the solid product. The product was then dried at 50 °C under a nitrogen atmosphere for 10 h to obtain the MOF composite material loaded with the dual repair agent. The mass ratio of (2,4,6-trioxotriazine-1,3,5(2H,4H,6H)-triyl)tris(hexamethylene)isocyanate, γ-aminopropyltriethoxysilane, and UiO-66 type cerium-doped zirconium-based MOFs support material is 1:0.2:1. Step 3: The MOFs composite material loaded with dual repair agents obtained in Step 2, polyurethane acrylate, dipentaerythritol hexaacrylate, trimethylolpropane triacrylate, photoinitiator 2-hydroxy-2-methyl-1-phenylpropanone, and leveling agent polyether-modified polydimethylsiloxane are added to a mixed solvent and stirred and dispersed at 2000 r / min for 30 min at 35°C to obtain a self-healing coating material based on MOFs. In this design, the mass ratio of the MOFs composite material loaded with dual repair agents to polyurethane acrylate is 1:15; the amount of dipentaerythritol hexaacrylate is 3% of the mass of polyurethane acrylate; the amount of trimethylolpropane triacrylate is 1% of the mass of polyurethane acrylate; the amount of photoinitiator 2-hydroxy-2-methyl-1-phenylpropanone is 0.5% of the mass of polyurethane acrylate; the amount of leveling agent polyether-modified polydimethylsiloxane is 0.1% of the mass of polyurethane acrylate; and the amount of mixed solvent is such that the solid content of the MOFs-based self-healing coating material is 40%. All the raw materials used in Example 2 were the same as those used in Example 1.

[0027] Example 3 This embodiment discloses a method for preparing a self-healing coating material based on MOFs, including the following steps: Step 1: Anhydrous zirconium tetrachloride and cerium nitrate hexahydrate are mixed at a molar ratio of 1:0.5 and then added to N,N-dimethylformamide to make the concentration of zirconium tetrachloride in the mixed metal salt solution 0.15 mol / L. The mixture is stirred at 400 r / min for 60 min at 35 °C to obtain the mixed metal salt solution. Then, terephthalic acid, at a molar ratio twice that of the sum of anhydrous zirconium tetrachloride and cerium nitrate hexahydrate, is added to N,N-dimethylformamide to make the concentration of terephthalic acid in the organic ligand solution 0.2 mol / L. The mixture is stirred at 400 r / min for 30 min at room temperature to obtain the organic ligand solution. The organic ligand solution was added dropwise to the mixed metal salt solution. After the addition was complete, the mixture was stirred at 400 r / min for 120 min at room temperature. The mixture was then transferred to a stainless steel hydrothermal reactor lined with polytetrafluoroethylene. After sealing, the mixture was reacted at 120℃ for 6 h. After naturally cooling to room temperature, the solid product was obtained by centrifugation. The solid product was washed three times with N,N-dimethylformamide, with each wash volume being 10 times the volume of the solid product. The solid product was then washed three times with methanol, with each wash volume being 10 times the volume of the solid product. The solid product was dried at 100℃ in air for 24 h to obtain the UiO-66 type cerium-doped zirconium-based MOF support material. Step two: The UiO-66 type cerium-doped zirconium-based MOF support material obtained in step one is added to n-hexane at a mass-to-volume ratio of 1 g / 80 mL. The mixture is stirred at 35°C and 400 r / min for 30 min to form a homogeneous suspension. (2,4,6-trioxotriazine-1,3,5(2H,4H,6H)-triyl)tris(hexamethylene)isocyanate is added to the suspension as a hexane dilution. The (2,4,6-trioxotriazine-1,3,5(2H,4H,6H)-triyl)tris(hexamethylene)isocyanate in the hexane dilution... A 1,3,5(2H,4H,6H)-triyl)tri(hexamethylene)isocyanate was mixed with n-hexane at a volume ratio of 1:5. The mixture was stirred at 400 r / min for 8 h at 30 °C. After stirring, γ-aminopropyltriethoxysilane was added, and stirring was continued at 400 r / min for 4 h at 30 °C. After stirring, the solid product was obtained by centrifugation and washed three times with n-hexane, each time with an amount of 8 times the volume of the solid product. The product was then dried at 50 °C under a nitrogen atmosphere for 10 h to obtain the MOF composite material loaded with the dual repair agent. The mass ratio of (2,4,6-trioxotriazine-1,3,5(2H,4H,6H)-triyl)tris(hexamethylene)isocyanate, γ-aminopropyltriethoxysilane, and UiO-66 type cerium-doped zirconium-based MOFs support material is 3:0.8:1. Step 3: The MOFs composite material loaded with dual repair agents obtained in Step 2, polyurethane acrylate, dipentaerythritol hexaacrylate, trimethylolpropane triacrylate, photoinitiator 2-hydroxy-2-methyl-1-phenylpropanone, and leveling agent polyether-modified polydimethylsiloxane are added to a mixed solvent and stirred and dispersed at 2000 r / min for 30 min at 35°C to obtain a self-healing coating material based on MOFs. In this process, the mass ratio of the MOFs composite material loaded with dual repair agents to polyurethane acrylate is 1:35; the amount of dipentaerythritol hexaacrylate is 10% of the mass of polyurethane acrylate; the amount of trimethylolpropane triacrylate is 5% of the mass of polyurethane acrylate; the amount of photoinitiator 2-hydroxy-2-methyl-1-phenylpropanone is 2% of the mass of polyurethane acrylate; the amount of leveling agent polyether-modified polydimethylsiloxane is 0.5% of the mass of polyurethane acrylate; and the amount of the mixed solvent is such that the solid content of the MOFs-based self-healing coating material is 55%. All the raw materials used in Example 3 were the same as those used in Example 1.

[0028] Comparative Example 1 This comparative example discloses a method for preparing a self-healing coating material based on MOFs. The only difference from the example is that when preparing the MOFs carrier material, the metal salt solution contains only zirconium ions, and the molar amount of terephthalic acid is twice the molar amount of zirconium ions, while other conditions remain unchanged.

[0029] Comparative Example 2 This comparative example discloses a method for preparing a self-healing coating material based on MOFs. The only difference from the example is that when preparing the MOFs carrier material, the metal salt solution contains only cerium ions, and the molar amount of terephthalic acid is twice the molar amount of cerium ions, while other conditions remain unchanged.

[0030] Comparative Example 3 This comparative example discloses a method for preparing a self-healing coating material based on MOFs. The only difference from Example 1 is that in step two, (2,4,6-trioxotriazine-1,3,5(2H,4H,6H)-triyl)tris(hexamethylene)isocyanate and γ-aminopropyltriethoxysilane are simultaneously added to the hexane suspension of the MOFs carrier material. All other conditions (including feed ratio, temperature, time, solvent amount, etc.) are exactly the same as in Example 1.

[0031] Characterization and Testing I. Characterization: (1) The morphology of the UiO-66 type cerium-doped zirconium-based MOFs support material prepared in Example 1 was observed using SEM (scanning electron microscope), such as... Figure 1 As shown, the MOF support has an octahedral structure and is a UiO-66 type metal-organic framework material; (2) The MOF support materials prepared in Example 1 and Comparative Examples 1-2 were characterized using XRD (X-ray diffraction), such as... Figure 2 As shown, the MOFs support material prepared in Comparative Example 1 exhibits strong diffraction peaks at 2θ = 7.38°, 8.52°, 12.06°, 14.15°, and 14.78°, corresponding to the (111), (200), (220), (311), and (222) crystal planes, respectively, indicating that it has a typical UiO-66 crystal structure. The MOFs support material prepared in Comparative Example 2 exhibits diffraction peaks at 2θ = 7.3°, 8.2°, 11.6°, 13.6°, and 14.3°, corresponding to the (111), (200), (220), (311), and (222) crystal planes, but its diffraction peak positions are lower than those of UiO-66-Zr, and the peak intensity is weaker. This is due to the Ce... 3+ The radius is larger. The diffraction peaks of the MOFs support materials prepared in Example 1 and Comparative Examples 1-2 are generally shifted to the left because of the larger Ce radius. 3+ Partially replaced the smaller radius Zr 4+This leads to lattice expansion, confirming the successful introduction of cerium ions into the metal node formation (Ce). x Zr 6-x The structure is O4(OH)4.

[0032] II. Test: The performance of the MOF-based self-healing coating material samples prepared in Examples 1-3 and Comparative Examples 1-2 was measured. By comparing the differences in adhesion, self-healing efficiency, and mechanical properties between the self-healing coating materials prepared in Examples 1-3 and Comparative Examples 1-2, the effect of the cerium-doped zirconium-based bimetallic MOF carrier material and its spatial partitioned loading design on improving the self-healing performance and overall performance of the coating was verified, as follows: (1) Adhesion and self-healing efficiency test: The MOF-based self-healing coating materials prepared in Examples 1-3 and Comparative Examples 1-2 were coated onto the surface of PET release films (75 μm thick, surface dyn value 42-46 dyn / cm), with a coating thickness of 50 μm (wet film). The coatings were then sequentially cured under ultraviolet light (365 nm, 300 mW / cm²). 2 The self-healing coating sample was obtained by treating it with nitrogen protection (90s) and heat curing (vacuum drying at 80℃ for 2h).

[0033] Referring to standard GB / T 39182-2020 "Test Method for Self-Healing Performance of Self-Healing Coatings", a Vickers microhardness tester (load 200g, hold for 10s) was used to create scratches approximately 30μm wide on the coating surface. The scratched coating sample was then placed in a 60℃ oven for 60min, and the width change of the scratch before and after healing was observed using an optical microscope. The self-healing efficiency was calculated using the following formula: Self-healing efficiency (%) = (scratch width before healing - scratch width after healing) / scratch width before healing × 100%. Five scratches at different locations were tested for each sample group, and the average value was taken. Referring to standard ASTM D3359, a grid was etched on the cured coating surface using the cross-cut method (1 mm grid spacing, 10×10 grids). Pressure-sensitive adhesive tape (3M 600 type) was then applied to the grid area and quickly peeled off at a 60° angle. The adhesion grade was determined based on the percentage of residual area of ​​the coating on the substrate surface (5B: residual area ≥95%; 4B: residual area 85%-94%; 3B: residual area 65%-84%; 2B: residual area 35%-64%; 1B: residual area <35%).

[0034] (2) Tensile strength recovery rate test after scratch repair: The MOF-based self-healing coating materials prepared in Examples 1-3 and Comparative Examples 1-2 were respectively coated onto the surface of a PET film (75 μm thick) coated with a polysiloxane release agent, with a coating thickness of 50 μm (wet film), and then sequentially cured under ultraviolet light (365 nm, 300 mW / cm²). 2 The self-healing coating samples were obtained by heat curing (90s, nitrogen protection) and drying at 80℃ for 2 hours. Following ASTM D638, the coating samples were prepared into dumbbell-shaped standard specimens (75mm total length, 25mm gauge length, 6mm width). After immersion in deionized water (room temperature, 24 hours), the PET release film was peeled off, and the specimens were allowed to air dry at room temperature. A cutter was used to make scratches approximately 50% of the coating thickness in the gauge length region of the specimen. The tensile strength of the specimens before and after repair (60℃ × 60min) was tested using a universal tensile testing machine (Instron 5967). The tensile strength recovery rate was calculated using the following formula: Tensile strength recovery rate (%) = tensile strength after repair / original tensile strength × 100%. Five specimens were tested for each group of samples, and the average value was taken. The test results are shown in Table 1: Table 1 As shown in Table 1, the coating material prepared by this invention exhibits excellent self-healing efficacy and adhesion. The self-healing efficiency of Examples 1-3 all exceeded 87%, and the tensile strength recovery rate all exceeded 82%. The self-healing coatings in these examples not only achieved surface morphology healing after scratch damage, but also effectively restored the mechanical properties of the damaged area. A strong positive correlation was observed between the tensile strength recovery rate and the self-healing efficiency, further verifying the crucial role of the spatial partitioning load design of this invention in maintaining the activity of the repair agent and ensuring chemical healing of the damaged interface. The adhesion of Examples 1-3 was the highest grade 5B because the urethane groups (-NHCOO-) in the polyurethane acrylate coating can form intermolecular hydrogen bonds with the polar groups on the PET surface. Simultaneously, the Zr on the surface of the MOF particles... 4+ and Ce 3+ The cerium sites form coordination bonds with the carbonyl oxygen in the polyurethane acrylate. The synergistic effect of these two chemical interactions endows the coating with excellent interfacial bonding strength between the coating and the PET substrate; therefore, the adhesion in Examples 1-3 all achieves a 5B grade. Comparative Example 1, compared to Example 1, aims to verify the necessity of cerium sites for achieving ordered anchoring of silane molecules. In a Zr-containing... 4+ In MOFs with specific sites, although isocyanates preferentially occupy zirconium sites within the pores, the amino functional groups of subsequently added γ-aminopropyltriethoxysilane interact with the Zr sites inside and outside the pores. 4+Non-specific coordination exists in all cases. This disordered competitive coordination prevents silane molecules from being selectively enriched on the outer surface of MOFs as in this invention, and instead causes them to be randomly distributed inside and outside the pores. This directly leads to two consequences: (1) an ordered molecular barrier layer of silane cannot be formed at the pore entrance, and isocyanate is prone to leakage and deactivation during subsequent curing; (2) the lack of ordered modification of silane on the outer surface prevents the formation of an efficient chemical bonding interface between MOF particles and the polymer matrix, thus significantly reducing self-healing efficiency and adhesion. Comparative Example 2 aims to verify the key role of zirconium sites in the stable loading of isocyanate molecules. In a system containing only Ce 3+ In MOFs at the cerium site, although the isocyanate added first can attach to the cerium site through coordination, the coordination stability of this is much lower than that of Zr. 4+ -NCO system. More importantly, since the cerium sites inside and outside the pores are of the same type, the later-added γ-aminopropyltriethoxysilane will compete with the already loaded isocyanate for the same type of cerium sites, resulting in the replacement of some isocyanate and premature release. In addition, the framework stability of pure cerium MOFs is poor, which exacerbates the unintended leakage of isocyanate during the coating curing process. Therefore, Comparative Example 2 lacks both the stable anchoring function of isocyanate and the partitioning barrier function of silane, resulting in the lowest self-healing efficiency and adhesion. At the same time, the decrease in adhesion in Comparative Example 3 further reveals another structural defect of the simultaneous feeding mode. γ-aminopropyltriethoxysilane plays a dual role in the design of this invention: (1) forming a molecular barrier layer at the pore entrance to protect the isocyanate anchored in the pore; (2) the triethoxysilane group at the other end of its molecule can be hydrolyzed and condensed to form a siloxane network during the coating curing process. In the simultaneous feeding mode of Comparative Example 3, γ-aminopropyltriethoxysilane was adsorbed in large quantities onto the cerium sites at the pore entrance of MOFs due to its diffusion rate advantage. However, this adsorption was not the ordered and uniform monolayer anchoring expected in this invention, but rather tended to be disordered stacking, which resulted in: (1) the active end portion of the γ-aminopropyltriethoxysilane molecule that should have been exposed to the outside for bonding with the polymer matrix was buried in the stacked layer at the pore entrance, reducing its effective utilization rate as an interfacial coupling agent; (2) because γ-aminopropyltriethoxysilane occupied the cerium sites in advance, the outer surface of MOFs failed to form an ideal uniform modification layer, resulting in exposed areas on the surface of MOF particles that were not covered by γ-aminopropyltriethoxysilane. The exposed MOF surface can only be physically bonded to the polyurethane acrylate matrix by weak van der Waals forces, and cannot form a dense covalent or coordination network through the chemical bridging of γ-aminopropyltriethoxysilane, which leads to a decrease in the interfacial bonding strength of MOF particles in the polymer matrix.

[0035] The above results demonstrate that the present invention achieves a significant improvement in coating self-healing efficiency and interfacial bonding strength through the following three levels of synergistic design: (1) Cerium doping introduces bimetallic nodes, providing differentiated anchoring points for the two repair agents; (2) The stepwise feeding sequence ensures that isocyanate preferentially anchors to zirconium sites on the inner wall of the pores, and silane coupling agent occupies cerium sites on the outer surface, achieving spatial partitioning loading; (3) Cerium sites simultaneously act as chemical bonding bridges between MOFs and the polymer matrix. Comparative Examples 1-3 verify the indispensability of the above design elements from different perspectives—the absence of cerium sites (Comparative Example 1), the absence of zirconium sites (Comparative Example 2), and the disruption of the stepwise feeding sequence (Comparative Example 3) all lead to a significant decrease in self-healing efficiency and adhesion. Among them, the results of Comparative Example 3 further confirm the key role of the stepwise feeding sequence in achieving spatial partitioning loading.

[0036] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions, and variations can be made to these embodiments without departing from the principles and spirit of the invention. Defined by the appended claims and their equivalents.

Claims

1. A method for preparing a self-healing coating material based on MOFs, characterized in that, Includes the following steps: Step one involves reacting zirconium salts and cerium salts with terephthalic acid to prepare UiO-66 type cerium-doped zirconium-based MOFs support materials. The specific preparation method includes: Zirconium and cerium salts were dissolved in N,N-dimethylformamide to obtain a mixed metal salt solution; terephthalic acid was dissolved in N,N-dimethylformamide to obtain an organic ligand solution; the organic ligand solution was added dropwise to the mixed metal salt solution, stirred, and then transferred to a reaction vessel. After the reaction was completed, the mixture was cooled, centrifuged, washed, and dried to obtain UiO-66 type cerium-doped zirconium-based MOFs support material. The molar ratio of zirconium salt to cerium salt is 1:(0.1-0.5), the molar amount of terephthalic acid in the organic ligand solution is twice the sum of the molar amounts of zirconium salt and cerium salt in the mixed metal salt solution, and the reaction conditions are 6-18 h at a temperature of 80-120℃. Step 2: Disperse the UiO-66 type cerium-doped zirconium-based MOFs support material in n-hexane, add (2,4,6-trioxotriazine-1,3,5(2H,4H,6H)-triyl)tris(hexamethylene)isocyanate, stir, and after stirring is completed, add γ-aminopropyltriethoxysilane and continue the reaction. After the reaction is completed, separate, wash and dry to obtain the MOFs composite material loaded with dual repair agents. The mass ratio of (2,4,6-trioxotriazine-1,3,5(2H,4H,6H)-triyl)tris(hexamethylene)isocyanate, γ-aminopropyltriethoxysilane, and UiO-66 type cerium-doped zirconium-based MOFs support material was (1-3):(0.2-0.8):

1. The stirring conditions were: stirring at 400-600 r / min for 3-8 h at a temperature of 30-50℃; and continued stirring at 400-600 r / min for 1-4 h at a temperature of 30-50℃. Step 3: The MOFs composite material loaded with dual repair agents is added to a mixed solvent along with polyurethane acrylate, dipentaerythritol hexaacrylate, trimethylolpropane triacrylate, photoinitiator and leveling agent. After dispersion treatment, a self-healing coating material based on MOFs is obtained. The mass ratio of MOFs composite material loaded with dual repair agents to polyurethane acrylate is 1:(15-35); the amount of dipentaerythritol hexaacrylate is 3%-10% of the mass of polyurethane acrylate; the amount of trimethylolpropane triacrylate is 1%-5% of the mass of polyurethane acrylate; the amount of photoinitiator is 0.5%-2% of the mass of polyurethane acrylate; and the amount of leveling agent is 0.1%-0.5% of the mass of polyurethane acrylate.

2. The method for preparing a self-healing coating material based on MOFs according to claim 1, characterized in that, The zirconium salt includes zirconium tetrachloride, and the cerium salt includes cerium nitrate. When preparing the mixed metal salt solution, the amount of N,N-dimethylformamide used is such that the concentration of zirconium salt in the mixed metal salt solution is 0.05-0.15 mol / L.

3. The method for preparing a self-healing coating material based on MOFs according to claim 1, characterized in that, When preparing the organic ligand solution, the amount of N,N-dimethylformamide used is such that the concentration of terephthalic acid in the organic ligand solution is 0.05-0.2 mol / L.

4. The method for preparing a self-healing coating material based on MOFs according to claim 1, characterized in that, In step three, the photoinitiator is 2-hydroxy-2-methyl-1-phenylpropanone, the leveling agent is polyether-modified polydimethylsiloxane, and the mixed solvent is prepared by mixing butyl acetate and propylene glycol methyl ether acetate in a volume ratio of (3-1):1; the amount of the mixed solvent is such that the solid content of the MOF-based self-healing coating material is 40%-55%.

5. A self-healing coating material based on MOFs, characterized in that, The self-healing coating material based on MOFs was prepared using the preparation method described in any one of claims 1-4.

6. The application of the MOF-based self-healing coating material as described in claim 5 on a paint protection film.

Citation Information

Patent Citations

  • Flame-retardant self-repairing waterborne polyurethane composite coating agent as well as preparation method and application thereof

    CN114560983A

  • Car paint protective film with scratch self-repairing function and preparation method thereof

    CN122325966A